Novel Cross-Talk between Three Cardiovascular Regulators: Thrombin Cleavage Fragment of Jagged1 Induces Fibroblast Growth Factor 1 Expression and Release - Duarte, Maria (The American Society for Cell Biology, 2008)
Angiogenesis is controlled by several regulatory mechanisms, including the Notch and fibroblast growth factor (FGF) signaling pathways. FGF1, a prototype member of FGF family, lacks a signal peptide and is released through an endoplasmic reticulum–Golgi-independent mechanism. A soluble extracellular domain of the Notch ligand Jagged1 (sJ1) inhibits Notch signaling and induces FGF1 release. Thrombin, a key protease of the blood coagulation cascade and a potent inducer of angiogenesis, stimulates rapid FGF1 release through a mechanism dependent on the major thrombin receptor protease-activated receptor (PAR) 1. This study demonstrates that thrombin cleaves Jagged1 in its extracellular domain. The sJ1 form produced as a result of thrombin cleavage inhibits Notch-mediated CBF1/Suppressor of Hairless [(Su(H)]/Lag-1–dependent transcription and induces FGF1 expression and release. The overexpression of Jagged1 in PAR1 null cells results in a rapid thrombin-induced export of FGF1. These data demonstrate the existence of novel cross-talk between thrombin, FGF, and Notch signaling pathways, which play important roles in vascular formation and remodeling.